JSE 29:1 Editorial - Braude, Stephen (Journal of Scientific Exploration, 2015)
It's probably no secret to readers of this Journal that working in areas of frontier science can very easily test one's character and bring out the best and worst of human behavior. I mention this now because a few months ago the journal Studies in History and Philosophy of the Biological and Biomedical Sciences published a significant new issue (Volume 48, Part A). It contains a lengthy special section on psychical research, guest-edited by Andreas Sommer. I'll probably comment again about this journal issue in later Editorials, but this time I want to focus on the first paper to catch my attention. Not surprisingly, I suppose, it was written by a philosopher, Ian James Kidd from Durham University, and it boasted the intriguing title, "Was Sir William Crookes epistemically virtuous?" (Kidd 2014).